2017
DOI: 10.1177/0260106017737014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-season dietary intake of professional soccer players

Abstract: The dietary intake of professional soccer players was adequate in energy, but inadequate in macro and micronutrients, which suggests the need to improve nutritional practices to sustain the physical demands of soccer during pre-season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 52 publications
5
52
1
4
Order By: Relevance
“…The majority of studies included in this review included team sport athletes competing professionally and semi-professionally in Australia ( n = 255) [3,25,26,33,43] and Spain ( n = 81) [28,29,30,36], with the remaining studies including athletes from Europe (not-specified) ( n = 34) [10,27], England ( n = 30) [23,34], America ( n = 26) [32,38], Canada ( n = 25) [39], Brazil ( n = 19) [37], Netherlands ( n = 14) [24], South Africa ( n = 11) [35], United Kingdom ( n = 10) [2], and Mexico ( n = 6) [31,37]. The majority of studies included in this review reported the dietary intakes of professional team sport athletes [2,3,10,23,24,26,27,28,29,31,33,34,36,37], with additional studies exploring dietary intake of semi-professional team sport athletes [32,35,38,39] and studies exploring the dietary intakes of a combination of sports [25,30,43]. Studies included a range of team sport athletes with the majority of studies reporting on the dietary intakes of football athletes ( n = 210) [23,24,25,28,30,31,34,37], followed by Australian football ( n = 139) [3,26,43].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies included in this review included team sport athletes competing professionally and semi-professionally in Australia ( n = 255) [3,25,26,33,43] and Spain ( n = 81) [28,29,30,36], with the remaining studies including athletes from Europe (not-specified) ( n = 34) [10,27], England ( n = 30) [23,34], America ( n = 26) [32,38], Canada ( n = 25) [39], Brazil ( n = 19) [37], Netherlands ( n = 14) [24], South Africa ( n = 11) [35], United Kingdom ( n = 10) [2], and Mexico ( n = 6) [31,37]. The majority of studies included in this review reported the dietary intakes of professional team sport athletes [2,3,10,23,24,26,27,28,29,31,33,34,36,37], with additional studies exploring dietary intake of semi-professional team sport athletes [32,35,38,39] and studies exploring the dietary intakes of a combination of sports [25,30,43]. Studies included a range of team sport athletes with the majority of studies reporting on the dietary intakes of football athletes ( n = 210) [23,24,25,28,30,31,34,37], followed by Australian football ( n = 139) [3,26,43].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included in this review reported the dietary intakes of professional team sport athletes [2,3,10,23,24,26,27,28,29,31,33,34,36,37], with additional studies exploring dietary intake of semi-professional team sport athletes [32,35,38,39] and studies exploring the dietary intakes of a combination of sports [25,30,43]. Studies included a range of team sport athletes with the majority of studies reporting on the dietary intakes of football athletes ( n = 210) [23,24,25,28,30,31,34,37], followed by Australian football ( n = 139) [3,26,43]. Across the remaining studies, other team sport athletes represented in this review include; rugby union ( n = 70) [10,27,33,35], ice-hockey ( n = 25) [39], wheelchair basketball ( n = 17) [29], American football ( n = 15) [32], handball ( n = 14) [36], volleyball ( n = 11) [38], rugby league ( n = 10) [2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations